2014
DOI: 10.1038/srep03805
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic nanostructures to enhance catalytic performance of zeolites under visible light

Abstract: Light absorption efficiency of heterogeneous catalysts has restricted their photocatalytic capability for commercially important organic synthesis. Here, we report a way of harvesting visible light efficiently to boost zeolite catalysis by means of plasmonic gold nanoparticles (Au-NPs) supported on zeolites. Zeolites possess strong Brønsted acids and polarized electric fields created by extra-framework cations. The polarized electric fields can be further intensified by the electric near-field enhancement of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 50 publications
0
34
0
2
Order By: Relevance
“…24,25 We have found that Au-NPs can significantly enhance zeolite photocatalysis with high product selectivity. 26,27 This research aims to develop new catalysts materials and innovative process. The plasmonic structure of Au-HYT was originally explored and firstly used for cellulose conversion under light irradiation.…”
Section: Sustainable Conversion Of Cellulosic Biomass To Chemicals Unmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 We have found that Au-NPs can significantly enhance zeolite photocatalysis with high product selectivity. 26,27 This research aims to develop new catalysts materials and innovative process. The plasmonic structure of Au-HYT was originally explored and firstly used for cellulose conversion under light irradiation.…”
Section: Sustainable Conversion Of Cellulosic Biomass To Chemicals Unmentioning
confidence: 99%
“…This is feasible because light irradiation can intensify the strongly polarised electrostatic fields of zeolite extra-framework ions. 26,27 Table 1 showed the results of cellulose conversion with various catalysts, including Au-HYT, Au-YT, HYT, YT, HY and HT. The conversion of cellulose proceeded effectively on these catalysts even at mild reactive conditions.…”
Section: Sustainable Conversion Of Cellulosic Biomass To Chemicals Unmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as light-harvesting is concerned, most of efforts have been focused on extending the photo-responsive region of photocatalysts to match the utmost of solar energy. The landmark cases, such as N-doped TiO 2 photocatalysts20, plasmonic photocatalysts2122, morphology modification2324252627, composite photocatalysts28293031, TiO 2 films32, were developed to make the photocatalysts to be effective under Vis light.…”
mentioning
confidence: 99%
“…4 shows the change in discharge current and GDLE intensity with pressure at U 0 = 750 V. The current values increase when the electric field increases for a constant pressure. We suggested that electron emission occurred not only from the surface but also from the cross-sectional surface of porous ZC [22]; thus, electron emission is more increased when using ZC ir . A gas discharge is initiated when a high concentration of electrons from a Si in zeolite framework, Si-O-Si bridging, and water vapor in the pores on the zeolite surface is combined with an anomalously high E in the pores.…”
Section: Resultsmentioning
confidence: 90%